Forensic science a sociological introduction - Lawless, Christopher (Routledge/Taylor & Francis Group, 2016)
This book addresses a significant gap in the literature and provides a comprehensive overview of the sociology of forensic science. Drawing on a wealth of international research and case studies, this book explores the intersection of science, technology, law and society and examines the production of forensic knowledge.